2000
DOI: 10.1128/jvi.74.19.8946-8952.2000
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Genital Tract Inflammation on Human Immunodeficiency Virus Type 1 V3 Populations in Blood and Semen

Abstract: We have examined cell-free viral populations in the blood plasma and seminal plasma compartments of men infected with subtype C human immunodeficiency virus type 1 (HIV-1) using the V3-specific heteroduplex tracking assay (V3-HTA). We studied two cohorts of subjects who had visited either a sexually transmitted disease (STD) clinic for genital tract inflammation in the form of urethritis (n ‫؍‬ 43) or a dermatology clinic (controls, n ‫؍‬ 14) in Malawi. We have previously shown that the presence of urethritis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
67
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 31 publications
4
67
0
2
Order By: Relevance
“…These data provide strong evidence for the presence of distinct populations of HIV-1 replicating in each site. Although we did not discern sequences that conferred different phenotypes on the viruses in each compartment, such differences have been observed (8,9,24,44,54). The detailed documentation of HIV-1 compartmentalization presented here underscores the potential for distinct, clinically relevant characteristics such as antiretroviral resistance or coreceptor usage in separate, biologically significant compartments.…”
Section: Discussionmentioning
confidence: 91%
“…These data provide strong evidence for the presence of distinct populations of HIV-1 replicating in each site. Although we did not discern sequences that conferred different phenotypes on the viruses in each compartment, such differences have been observed (8,9,24,44,54). The detailed documentation of HIV-1 compartmentalization presented here underscores the potential for distinct, clinically relevant characteristics such as antiretroviral resistance or coreceptor usage in separate, biologically significant compartments.…”
Section: Discussionmentioning
confidence: 91%
“…This suggests the V1/V2 region can reveal more diversity in transmitted variants than the V3 region. Therefore, we believe V1/V2 HTA is a more robust tool for describing a complex viral population than V3 HTA, which we have also used previously in this context (46). The detection of multiple variants in 50% of subjects is a minimum estimate since transmission of two variants with the same V1/V2-HTA pattern would be recorded as a single variant.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 ϩ T cell levels, viral loads, and GenBank accession numbers for the analyzed envelope genes are presented in Table 1. Previous analysis of viral RNA sequences in the seminal and blood plasma samples, performed first using a V3-specific heteroduplex tracking assay and then, more recently, using endpoint dilution PCR (i.e., single-genome amplification [SGA]) and sequence analysis, showed that a group of the seminal plasma-derived viral sequences from each of these five subjects formed a lineage genetically distinct from those of virus in the blood of the same subject (7,9). Now we have performed phenotypic analysis of a subset of the fulllength env genes amplified from each subject to determine the entry phenotype with respect to the ability to enter cells efficiently using low levels of CD4.…”
mentioning
confidence: 99%